Modernization of surfactant chemistry in the age of gemini and bio-surfactants: a review. Issue 112 (30th October 2015) - Mondal, Monohar Hossain; Malik, Susanta; Roy, Ankit; Saha, Rumpa; Saha, Bidyut
Abstract : This review contains elaborate discussions on the efficiencies of gemini and bio-surfactants as modern generation green chemicals in various fields. Abstract : Modern surfactant science demands chemistry which is benign by design. Efficient green chemicals like gemini surfactants along with natural resource derived bio-surfactants are thus most dependable in this case. In the search for less pollution and more ecologically beneficial solvents, more and more environmentally accepted trends are emerging every day into the market; species related to properties such as lower toxicity, higher biodegradability, chemical stability, environmental safety, efficient solubilization and of course, ease of recycling, can be vital tools. Bio-surfactants along with geminis are of great interest for their very efficient working ability, lower CMC and other up to date features that modern science desires for the betterment of mother nature. This review contains elaborate discussions on the efficiencies of gemini and bio-surfactants as modern generation green chemicals in various fields viz. in laboratory based kinetic experiments, electron transfer reactions, emulsification, solubilization, and agro-industrial and bio-medicinal fields which provides us with the hope of an amazing future prospect with these types of green chemicals.